Food-Pics_Extended—An Image Database for Experimental Research on Eating and Appetite: Additional Images, Normative Ratings and an Updated Review - Blechert, Jens; Lender, Anja; Polk, Sarah; Busch, Niko A.; Ohla, Kathrin (Frontiers in Psychology, 2019)
Our current environment is characterized by the omnipresence of food cues. The taste and smell of real foods—but also graphical depictions of appetizing foods—can guide our eating behavior, for example, by eliciting food craving and anticipatory cephalic phase responses. To facilitate research into this so-called cue reactivity, several groups have compiled standardized food image sets. Yet, selecting the best subset of images for a specific research question can be difficult as images and image sets vary along several dimensions. In the present report, we review the strengths and weaknesses of popular food image sets to guide researchers during stimulus selection. Furthermore, we present a recent extension of our previously published database food-pics, which comprises an additional 328 food images from different countries to increase cross-cultural applicability. This food-pics_extended stimulus database, thus, encompasses and replaces food-pics. Normative data from a predominantly German-speaking sample are again presented as well as updated calculations of image characteristics.